Horizontal inequality, COVID-19, and lockdown readiness: Evidence from India - Rachel M. Gisselquist; Anustup Kundu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
A growing body of research shows that COVID-19 both reflects and exacerbates existing inequalities. However, there are significant gaps in this research area with respect to 'horizontal' or group-based inequalities in Global South countries. Lack of group-disaggregated data often contributes. In this paper, we use available data to explore how horizontal inequality in India may influence COVID-19's impact through the differential impact of lockdown policies across caste and religious groups, as well as across states and urban-rural areas. In so doing, we build upon Egger et al. (2020)'s lockdown readiness index. India, the second most populous country in the world, is a relevant case for such analysis, not only because it has pronounced horizontal inequality, but also because it adopted an especially stringent lockdown policy. Our analysis illustrates stark differences in lockdown readiness across groups, which in turn could exacerbate existing horizontal inequalities.
Keywords: I14; I18; J15; Z13; 330; horizontal inequality; ethnic inequality; caste; India; COVID-19; coronavirus; lockdown